Pengaruh Atribut Produk dan Harga Terhadap Brand Switching Produk Smartphone Samsung Ke Merek Lain - Murni Atifah; Rose Rahmidani (Jurnal Ecogen, 2022)
The purpose of this study was to determine the effect of product attributes and price on brand switching on Samsung smartphone products at Padang State University. This research used causative form.The population in this research were students of State University of Padang. The Number of samples were decided base on William Cochran's. As many as 100 people and were chosen by using non probability sampling method and purposive sampling technic.Data were used is primer data were provided through questionnaire shared to students of State University of Padang based on predetermined criteria. Analysis method was used is multiple regression by using spss 26. The results showed that (1) product attributes had a significant effect on brand switching of Samsung smartphone products to other brands, (2) price had a significant effect on brand switching of Samsung smartphone products to other brands, (3) product attributes and prices had a significant effect on brand switching products Samsung smartphones to other brands. Keywords : product attributes, price, brand switching